Corneal curvature measurements utilizing a new swept-source optical coherence tomography Tomey OA-2000® and comparison with IOLMaster® 500 in pterygium patients - Hilmi, Mohd Radzi; Mohd Kamal, Khairidzan; Che Azemin, Mohd Zulfaezal; Ithnin, Mohd. Hafidz; Md Mustafa, Md Muziman Syah; Yusof @ Alias, Firdaus; Ahmad, Norsham (Fakultas Kedokteran Universitas Islam Sultan Agung, 2018)
Introduction: Corneal curvature (CC) is an important anterior segment parameter. This study compared CC measurements conducted with two optical devices in pterygium eyes. Methods: Sixty pterygium eyes of 30 patients were enrolled in this study. CC was measured three times with the optical biometer and topography-keratometer Tomey OA-2000 (Tomey Corporation, Nagoya, Japan), then with partial optical coherence interferometry (PCI) IOL Master 500 (Carl Zeiss Meditec, Dublin, CA) and data were statistically analysed. Results: The measurements revealed in a mean CC of 43.86 ± 1.57 D with Tomey OA-2000 and 43.84 ± 1.55 D with IOL Master. Distribution of data is normal, and no significance difference in CC values was detected (P = 0.952) between the two devices. Correlation between CC measurements was highly significant (r = 0. 99; P < 0.0001). The mean difference of CC values between devices was 0.017 D and 95% limit of agreement was -0.088 to 0.12. Duration taken for measurements with the standard biometer IOL Master was longer (55.17 ± 2.24 seconds) than with Tomey OA-2000 (39.88 ± 2.38 seconds) in automatic mode. Duration of manual measurement with Tomey OA-2000 in manual mode was shorter (28.57 ± 2.71 seconds). Conclusion: In pterygium eyes, CC measured with Tomey OA-2000 and IOL Master showed similar values, and high correlation was observed between these two devices. This shows that both devices can be used interchangeably. Tomey OA-2000 is better in terms of faster to operate and has its own topography systems.